FILSAFAT MANAJEMEN: LANDASAN ONTOLOGIS, EPISTEMOLOGIS, DAN AKSIOLOGIS DALAM ORGANISASI MODERN - Nuroini, Nazilatun; Rofiq, Ainur (Hijri, 2025)
?Management philosophy is often viewed as an abstract realm separate from day-to-day managerial practice. However, this research argues that it is the philosophical foundation that provides the strength and sustainability for every management action. This article aims to examine in depth the role of management philosophy through three main lenses: ontology, epistemology, and axiology, in responding to contemporary organizational challenges. The research method employed is a systematic qualitative literature study, collecting and analyzing primary and secondary sources from selected publications in the 2020-2025 period, supplemented by qualitative data from semi-structured interviews with ten management practitioners. The results reveal that organizations that consciously integrate philosophical reflection into their strategy and operations demonstrate higher resilience in facing disruption, improvement in ethical decision-making, and increased employee engagement. Ontological analysis reveals a shift in understanding the nature of organizations from mechanistic entities to adaptive living systems. Epistemological examination shows that valid management knowledge arises from the synthesis of empirical evidence, critical reflection, and contextual wisdom. Meanwhile, the axiological approach affirms that values such as justice, sustainability, and transparency are not merely complements but primary drivers of long-term performance. The discussion in this article connects these findings with classical and contemporary management theories, demonstrating that philosophy acts as a bridge connecting theory with practice, and fills the gap between technical efficiency and human meaning in work. This article concludes that neglecting the philosophical dimension in management is a form of strategic risk. Therefore, this article recommends that management education and leadership development strengthen the philosophical curriculum, and organizations encourage a culture of critical reflection to build a more resilient and meaningful future.??